2012
DOI: 10.1038/bjc.2012.65
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery pulsatility index: a predictor of methotrexate resistance in gestational trophoblastic neoplasia

Abstract: Background:Neo-angiogenesis is a hallmark of cancer. The aim of this study was to test the hypothesis, in a prospective patient cohort, that in low-risk gestational trophoblastic neoplasia (LR-GTN) the uterine artery pulsatility index (UAPI), a measure of tumour vascularity, can predict resistance to methotrexate chemotherapy (MTX-R).Methods:286 LR-GTN patients (Charing Cross Hospital (CXH) score 0–8, or FIGO score 0–6) were treated with methotrexate between January 2008 and June 2011 at CXH. During staging in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 22 publications
0
40
0
1
Order By: Relevance
“…The uterine artery pulsatility index (UAPI) is a Doppler ultrasound measure of tumour vascularity, and we have previously shown that a UAPI ≤1 (high vascularity) is an independent predictor of MTX‐R in women with low‐risk disease. The predicted risk of MTX‐R in women with a UAPI ≤1 and a FIGO score of 5–6 was >75%, suggesting that these women might benefit from initial EMA/CO therapy . However, a significant limitation of our previous two studies was that women with FIGO 5–6 GTN constituted only a small proportion (10%) of the overall patient cohorts (16/164 and 24/239 women) .…”
Section: Introductionmentioning
confidence: 78%
“…The uterine artery pulsatility index (UAPI) is a Doppler ultrasound measure of tumour vascularity, and we have previously shown that a UAPI ≤1 (high vascularity) is an independent predictor of MTX‐R in women with low‐risk disease. The predicted risk of MTX‐R in women with a UAPI ≤1 and a FIGO score of 5–6 was >75%, suggesting that these women might benefit from initial EMA/CO therapy . However, a significant limitation of our previous two studies was that women with FIGO 5–6 GTN constituted only a small proportion (10%) of the overall patient cohorts (16/164 and 24/239 women) .…”
Section: Introductionmentioning
confidence: 78%
“…When there is no response to sequential single-agent therapy, multiagent ChT should be initiated, and the EMA-CO regimen is the most commonly used multiagent ChT 4 . Recent studies suggest that a uterine artery pulsatility index equal to or lower than one predicts an increase in the risk of resistance to MTX/FA in women with low-risk GTN and may be useful in patient staging for first line therapy 44,45 . Prospective studies are underway evaluate this finding.…”
Section: Resistant or Recurrent Diseasementioning
confidence: 99%
“…In this case, uterine artery Doppler pulsatility index was less than 1, which is an independently validated predictor of methotrexate resistance in low-risk GTN. 24 Consistently, Architect showed a plateau, which is indicative of methotrexate resistance, whereas Immulite showed a decline in hCG.…”
Section: Discussionmentioning
confidence: 91%